Maternal-fetal attachment and Family Support among pregnant women in Yogyakarta - Endang Koni Suryaningsih; Fenny Nur Alvianty; Wantonoro Wantonoro (International Journal of Health Science and Technology, 2022)
Maternal-fetal attachment is crucial for a mother to establish a healthy psychological relationship with her unborn baby. This relationship progresses during the week of gestation. Many studies support the evidence of the impact of maternal-fetal attachment on mothers’ mental well-being during both antenatal and postnatal. For a baby, maternal-fetal attachment is essential to determine his development. Family, particularly the husband, plays an essential role in supporting the mother to experience positive maternal-fetal attachment during pregnancy. This study was to investigate the relationship between family support with maternal-fetal attachment among expectant mother. This sample was drawn using the purposive sampling method based on criteria that include mothers in their third trimester, mothers with any age range, mothers with no complications during the current pregnancy, and mothers who stay together with their husbands and or family. Seventy-seven expectant mothers completed the Indonesian version of the Prenatal Attachment Inventory and family support questionnaires. Kendal tau was applied to calculate the statistical relationship between two variables (p0.05). The results showed that more than 50% mother obtained support from their family, and more than 50% mother have high score of maternal-fetal attachment. There were a significant relationship between family support and maternal-fetal attachment (p 0.000). The conclusion of this study was that there were a significant relationship between family support with maternal-fetal attachment. This finding provides evidence of the significant role of family support for maternal mental well-being through maternal-fetal attachment during pregnancy. Therefore, healthcare providers have to invite the husband or family to engage in support for the mother during their pregnancy.